Effects of fluctuations on correlation functions in inhomogeneous mixtures - Ciach, null (2020)
Approximate expressions for correlation functions in binary inhomogeneous mixtures are derived in a framework of the mesoscopic theory [Ciach A., Mol. Phys., 2011, 109, 1101]. Fluctuation contribution is taken into account in a Brazovskii-type approximation. Explicit results are obtained for two model systems. In the two models, the diameters of the hard cores of particles are equal, and the interactions favour a periodic arrangement of alternating species A and B. However, the optimal distance between the species A and B is much different in the two models. Theoretical results for different temperature and volume fractions of the two components are compared with the results of Monte Carlo simulations, and the structure is illustrated by simulation snapshots. Despite different interaction potentials and different length scale of the local ordering, properties of the correlation functions in the two models are very similar.